Enhanced upconversion from Er 3+ /Yb 3+ co-doped alkaline earth aluminates phosphor in presence Zn 2+ : A comparative study - Choudhary A.K.; Dwivedi A.; Bahadur A.; Rai S.B. (My University, 2025)
In the present work, the upconversion emission spectra of Er 3+ /Yb 3+ co-doped CaAl 2 O 4 (CAO), SrAl 2 O 4 (SAO) and BaAl 2 O 4 (BAO) phosphor samples have been studied in absence and presence of Zn 2+ . The samples were synthesized using high temperature solid state reaction technique at 1623 K. The X-ray diffraction (XRD) measurements have been carried out to verify the pure phase formation in all the three cases. Whereas the CAO and SAO samples show the monoclinic phase, the BAO sample shows hexagonal phase. The surface morphology of the three phosphor samples has been studied by scanning electron microscopy (SEM) technique. The Fourier-transform infrared (FTIR) and Raman measurements show the vibrational bands due to different groups present in the samples. The upconversion emission spectra of all the three samples show green and red emissions bands due to Er 3+ ion on excitation with 980 nm laser. However, it is interesting to note that CAO phosphor emits very intense green and weak red emissions, the SAO and BAO phosphors give intense red and weak green emissions. However, the upconversion emission intensity (green as well as red both) in all the three samples is enhanced several times in presence of Zn 2+ ions. The mechanism involved in UC emissions has been explained by partial energy level diagram. © 2019